Buckling mechanism of cable-stiffened lattice shells with bolted connections. Issue 15 (November 2019) - Wang, Xi; Feng, Ruo-qiang; Yan, Gui-rong; Zhu, Bao-chen; Liu, Feng-cheng
The cable-stiffened lattice shell is a new structural system for its translucence and lighting. This article discusses the effect of the connections' behavior and geometric imperfection on the structural stability and reveals the buckling mechanism of the cable-stiffened lattice shell. The spring stiffness for bolted connections of cable-stiffened lattice shells is deduced from the spring in series model. The buckling mechanism of cable-stiffened lattice shells with three types of joints have been studied based on the prototypical static experiments of bolted connections. The decrease of bolted connections' stiffness would lead to the change in the displacement distribution for the lattice shell under its ultimate load. The buckling loads and initial structural stiffness of cable-stiffened lattice shells with shim-strengthened bolted joints are approximately 80% of those for cable-stiffened lattice shells with rigid joints. The result indicates that the buckling loads of cable-stiffened lattice shells with bolted connections decrease much more slowly than the decrease of bolted connections' stiffness. The cable-stiffened lattice shell with SBP connections is more sensitive to the initial geometric imperfection. Finally, a formula has been proposed for estimating buckling loads of elliptic paraboloid cable-stiffened lattice shells with bolted connections.